Association of Proprotein Convertase Subtilisin/Kexin Type 9 (PCSK9) Polymorphism with Atherosclerosis: A Bibliometric Analysis - Rafia; Basheer, Sehrish; Khalil, Adila; Hussain, Misbah (Current Trends in OMICS, 2025)
Bibliometric analysis offers a sophisticated approach to mapping the development and boundaries of a discipline. This study aimed to map global research trends on Proprotein Convertase Subtilisin or Kexin Type 9 (PCSK9) polymorphisms in atherosclerosis, an area with little previous investigation, using bibliometric analysis. PCSK9 is involved in the metabolism of cholesterol, impacting the risk of atherosclerotic cardiovascular disease (ASCVD). Understanding the relationship between PCSK9 polymorphisms and atherosclerosis mayhelp design suitable therapeutic strategies. Dimensions database was searched to retrieve research and review articles using query [TS = ((PCSK9 AND Polymorphism OR Variant) AND (Atherosclerosis))]. Articles published between 2004 and 2024 were included. VOS viewer software was used for data visualization and analysis. Total 816 research and review articles were retrieved. Research trend indicated a gradual rise in count of articles annually. Brigham and Women's Hospital, USA contributed the most in this research field. Robert Patrick Giugliano (Brigham and Women's Hospital, USA) and Marc Steven Sabatine (Brigham and Women's Hospital, USA) were the top contributors. In the discipline of atherosclerosis and cardiovascular diseases (CVDs), the high impacting journal is The European Heart Journal. Current research hot spots, such as hypercholesterolemia, PCSK9, atherosclerosis, statin therapy, and inflammation, were identified by a keyword analysis and major literature review. Recently, extensive interest in association of PCSK9 polymorphism with atherosclerosishas been explored internationally. Currently, the discipline is experiencing an upsurge in research with a focus on inflammation and coronary arteries.